THE EVOLUTION OF TYPE II DIABETES MELLITUS: HOW THE MALADAPTIVE DISEASE CONTINUES TO SURVIVE SELECTIVE PRESSURES. - AbdulelahAlmoteri, Khalid Alboloi, Mohammed Noor, HamoudAlmotary, DaefallahLaharbi, Fahad Almutairi, AbdulazizAlbalawi, AlaaDabbour (Chelonian Research Foundation, 2023)
Over twenty-five years of research into diabetes type two mellitus, a working hypothesis has formed to advance the development of precision therapy for this condition. Previous studies that used amplified genomic DNAs for genome-wide searches of human genes misled many researchers. However, a recent investigation used next-generation RNA sequencing to demonstrate a crucial down-regulation of two genes, TPD52L3 and NKX2-1. This compendium covers key principles for understanding the hypothesis, including glucose effectiveness, genetics, atomistic glucose and glucose transport, β-cell functions, insulin sensitivity, free fatty acids, cell membranes, membrane flexibility, and pre-diabetes type 2. Furthermore,this paper will evaluate the T2D enigma from a genetic and evolutionary standpoint with the aim of gaining insight into the reasons that underpin the growing genetic predisposition and positive natural selection of T2D.This paper will evaluate the T2D enigma from a genetic and evolutionary standpoint with the aim of gaining insight into the reasons that underpin the growing genetic predisposition and positive natural selection of T2D.This paper additionallyaddresses the 10 evolutionary questions associated with disease vulnerability. Key Words: Type two diabetes, insulin resistance, monogenic inheritance, polygenic subset, health outcomes.